Fibrinogenase for injection in the treatment of acute ischaemic stroke: a randomised clinical trial - Ma, Mengmeng; Fang, Jinghuan; Jiang, Xin; Liu, Qian; Guo, Jian; Chen, Ning; Zhang, Yang; Li, Yanbo; Li, Changling; Zhou, Rujiang; Li, Hao; Yu, Ming; et al. (Stroke and Vascular Neurology, 2025)
Background Fibrinogenase for injection is an effective antithrombotic agent for eligible patients with acute ischaemic stroke (AIS), but evidence regarding its treatment effects remains limited. This study aimed to evaluate the efficacy and safety of fibrinogenase for injection in patients with AIS who did not receive reperfusion therapies. Methods A multicentre, randomised, double-blind, placebo-controlled clinical trial was conducted at 12 hospitals in China. Inclusion criteria comprised patients aged 18–85 years with a diagnosis of AIS, an NIH Stroke Scale (NIHSS) score of 4 to 25 and within 72 hours of symptom onset. Eligible patients were randomly allocated in a 1:1 ratio to receive fibrinogenase for injection or placebo. The primary efficacy endpoint was the modified Rankin Scale (mRS) Score at 90 days after randomisation. Results Among 235 patients with AIS who were randomised, 233 were included in the intention-to-treat population (117 in the fibrinogenase for injection group and 116 in the placebo group). The mRS score at 90 days after randomisation was significantly lower in the fibrinogenase group (1 (0–2)) than in the placebo group (2 (1–3)), with a favourable shift in the distribution of mRS scores (OR 2.38, 95%CI 1.49 to 3.85; p<0.001). A significantly lower median NIHSS score at 90 days was observed in the fibrinogenase group (1 (0–2)) compared with the placebo group (2 (1–4)) (OR 1.95, 95%CI 1.23 to 3.10; p<0.001). The incidence of haemorrhagic events and mortality during treatment was comparable between the two groups. Conclusions In patients with AIS, treatment with fibrinogenase for injection was associated with improved 90-day functional outcomes compared with placebo. This clinical benefit was particularly evident among those who were randomised within 48 hours of symptom onset and in those with mild to moderate stroke due to large artery atherosclerosis or small artery occlusion.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Cerebral Infarction; Clinical Trial; Ischemic Stroke; Stroke